VERTICAL JUMP ENHANCEMENT WITH RESPECT TO VOLLEYBALL VERTICAL JUMP - MILO, Navot; GROSU, Emilia Florina; MILO, Michaela (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2017)
The purpose of next review is to present the knowledge gained about the mechanical and physiological aspects that responsible for vertical jump (VJ) height, as well as the general training methods for VJ enhancement, with specific reference to volleyball players. Several intertwined aspects determine VJ capacity: muscle power, neural properties and elastic properties of muscles and tendons. Three major methods for enhance VJ are discussed in this review: Plyometric training (PT), which involve jumping, hopping, and skipping and reinforces muscle's neural activity and the ability to restore elastic-energy; Electromyostimulation (EMS), which increases the ability to recruit muscles' motor units; And resistance training (RT), which is usually performed using weights and increases muscles' power generation. These methods complement one another and therefore present the best results when integrated. In addition, part of the reviewed studies claims for even better VJ enhancement when RT are performed in the VJ pattern. Therefore, ballistic RT and Olympic weight-lifting (snatch, clean and jerk) in relatively low resistance (30-50% of IRM) at high velocity are preferable as RT for VJ enhancement. The effect of PT and RT, when integrated into specific volleyball training, even increases VJ because this specific leg power training can be transferred more efficiently into a volleyball specific VJ.